2021
DOI: 10.1519/jsc.0000000000002888
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Knee Extensor Torque: Effect of Aging and Contraction Intensity

Abstract: Fiogbé, E, Vassimon-Barroso, V, Catai, AM, de Melo, RC, Quitério, RJ, Porta, A, and Takahashi, ACdM. Complexity of knee extensor torque: effect of aging and contraction intensity. J Strength Cond Res 35(4): 1050–1057, 2021—Assessing the knee extensors' torque complexity in older adults is relevant because these muscles are among the most involved in functional daily activities. This study aimed to investigate the effects of aging and isometric contraction intensity on knee extensor torque complexity. Eight you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…They observed a progressive decline in the complexity of index finger abduction force (measured using ApEn and DFA α) during low‐intensity isometric contractions (performed at 5, 10, 20 and 40% MVC) from young adults (aged 20–24 years) to old adults (aged 60–69 years) and older‐old adults (aged 75–90 years). These findings have been confirmed by several subsequent studies (Sosnoff & Newell 2006, 2008) and extended to low‐intensity (15–40% MVC) isometric knee extension contractions (Fiogbé et al., 2021). Taken together, these findings indicate that an age‐induced loss of muscle force complexity affects both small upper limb muscles associated with fine motor skills and large lower limb muscles associated with locomotion.…”
Section: Loss Of Complexity Hypothesissupporting
confidence: 72%
See 1 more Smart Citation
“…They observed a progressive decline in the complexity of index finger abduction force (measured using ApEn and DFA α) during low‐intensity isometric contractions (performed at 5, 10, 20 and 40% MVC) from young adults (aged 20–24 years) to old adults (aged 60–69 years) and older‐old adults (aged 75–90 years). These findings have been confirmed by several subsequent studies (Sosnoff & Newell 2006, 2008) and extended to low‐intensity (15–40% MVC) isometric knee extension contractions (Fiogbé et al., 2021). Taken together, these findings indicate that an age‐induced loss of muscle force complexity affects both small upper limb muscles associated with fine motor skills and large lower limb muscles associated with locomotion.…”
Section: Loss Of Complexity Hypothesissupporting
confidence: 72%
“…Several studies on ageing and disease have demonstrated changes in complexity in the absence of changes in the magnitude of fluctuations (Fiogbé et al., 2021; Vaillancourt & Newell, 2000), suggesting that they may hold potential in detecting sub‐clinical changes in motor control. Furthermore, complexity measures have been demonstrated to be tightly coupled to the neuromuscular fatigue process (Pethick et al., 2018) and exhibit the same exercise intensity domain‐specific behaviours as measures such as V̇normalO2, blood [lactate] and pH (Pethick et al., 2016; Pethick et al ., 2020; Poole et al., 2016).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Therefore, this reduction in torque complexity in frail group could be related to the loss of structural components, such as a reduction in the number of motor units, or changes in the coupling between them, for example in the reduction of synchrony in motor unit recruitment. 14 Torque complexity has been reported by Fiogbé et al 48 , who presented a reduction in knee extensor torque complexity in healthy older adults compared to young subjects. However, this is the first time it was verified that the presence of frailty syndrome caused greater reduction in torque complexity.…”
Section: Discussionmentioning
confidence: 78%
“…51 In this study, even frail older adults were able to respond adequately to requests for submaximal force maintenance, although they had a reduction in torque complexity. Fiogbé et al 48 compared the knee extensor torque complexity (at 15, 30 and 40% of MVC) in young subjects and healthy older adults. The findings were that although the older adults presented with a reduced complexity, the relationship with the increase in SIC was similar between older adults and young subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the knee extensor muscles of the dominant leg will be assessed using an isokinetic dynamometer (Biodex Multi joint System III; Biodex Medical System, Shirley, NY, USA), and the positioning for the acquisition of the signals according to a previous study. 25 Participants will carry out three maximal isometric voluntary contractions followed by three voluntary submaximal isometric knee extensions. The contraction intensities will be 15%, 30% and 40% of the highest maximal isometric voluntary contractions.…”
Section: Assessment Of Strength Of Knee Extensor Musclesmentioning
confidence: 99%